An Overview of Molecular Advances in Zoysiagrass. (16th August 2017) - Chandra, Ambika; Milla‐Lewis, Susana; Yu, Qingyi
Abstract : Zoysiagrass ( Zoysia spp. Willd.) is a perennial warm‐season grass adapted to the tropical and southern temperate regions of the world. Species of Zoysia and their interspecific hybrids are recognized for their low cultural requirements and tolerance to a wide array of biotic and abiotic stresses, and are widely used as turfgrass on golf courses, athletic fields, home lawns, and other recreational sites. Plant breeders predominantly use conventional breeding methods involving hybridization and phenotypic selection to make genetic improvements in zoysiagrass. Zoysia spp. are cross compatible, limiting phenotype‐based classification and identification. Zoysiagrass is also an open‐pollinated and polyploid species, which makes it a difficult molecular target. However, the recent influx of powerful molecular biology tools, genome sequencing, and genetic transformation will enable breeders to make more efficient, accurate, and targeted improvements. Compared with major agricultural crops such as wheat ( Triticum spp. L.), rice ( Oryza sativa L.), and maize ( Zea mays L.), as well as cool‐season turf or forage grasses such as ryegrass ( Lolium spp. L.) and fescues ( Festuca spp. L.), slow but recognizable molecular advancements have been made in zoysiagrasses, which will be covered in this article. Commitment by public and private sector to increased funding for molecular and genomic research in turfgrasses will enable researchers to take advantage of these new technologies to make more targeted and efficient genetic improvements in a reasonable period of time.